Benzo[a]pyrene degradation by soil filamentous fungi - Romero, Maria Cristina (2010)
The fungal ability to biotransform xenobiotics had received attention due to their dominance, ubiquity and different pathways that detoxificate aromatic hydrocarbons. The filamentous fungi Aspergillus flavus and Paecilomyces farinosus showed a significant degradation activity on benzo[a]pyrene with and without C16 as cosubstrate. 14CO2, 14C-volatile organic, 14C-extractable, 14C-nonextractable, 14C-biomass and 14C-aqueous fractions were determined with [7, 10]14C-BaP assays, with A. flavus, Cladosporium cladosporioides, Gliocladium viride, P. farinosus and Talaromyces rotundus. However, the activity of A. flavusand P. farinosus were higher. These non-ligninolytic fungi degraded BaP by cometabolism in C16 presence, were adapted to toxicants and dominant in polluted habitats, so they could play an important role in self- bioremediation processes.